Imidazolium salts as an alternative for anti-Leishmania drugs: Oxidative and immunomodulatory activities - Baldissera, Fernanda Giesel; Fazolo, Tiago; da Silva, Matheus Brasil; de Santana Filho, Paulo Cesar; da Silva, Vinícius Demétrio; Rivillo Perez, David Max; Klitzke, Joice Sandra; de Oliveira Soares, Eduardo Giovanni; Rodrigues Júnior, Luiz Carlos; Peres, Alessandra; Dallegrave, Eliane; Navegantes-Lima, Kely Campos; et al. (Frontiers in Immunology, 2023)
In this study we explored the previously established leishmanicidal activity of a complementary set of 24 imidazolium salts (IS), 1-n-hexadecylimidazole (C16Im) and 1-n-hexadecylpyridinium chloride (C16PyrCl) against Leishmania (Leishmania) amazonensis and Leishmania (Leishmania) infantum chagasi. Promastigotes of L. amazonensis and L. infantum chagasi were incubated with the compounds at 100 μM for 48 h and eight of them demonstrated leishmanicidal activity – C10MImMeS, C16MImPF6, C16MImBr, C16M2ImCl, C16M4ImCl, (C10)2MImCl, C16Im and C16PyrCl. These compounds were tested again against the promastigotes at concentrations ranging from 0.1 to 100 μM and the parasites survival was determined after 48 h. The effect of IS on reactive oxygen species production, mitochondrial membrane potential, membrane integrity and morphological alterations of promastigotes were determined, as well as on L. amazonensis-infected macrophages. Imidazolium salts cytotoxicity against macrophages and human erythrocytes were evaluated. The IS C10MImMeS, C16MImPF6, C16MImBr, C16M2ImCl, C16M4ImCl and (C10)2MImCl, and the compounds C16Im and C16PyrCl killed and inhibited the growth of promastigote forms of L. amazonensis and L. infantum chagasi in a concentration-dependent manner. These IS induced ROS production, mitochondrial dysfunction, membrane disruption and morphological alterations in infective forms of L. amazonensis and were able to kill intracellular amastigote forms in a very low concentration, being suggested as potential drug candidates against L. amazonensis. The study contributes to the understanding of the relationship structure-activity of IS against Leishmania.